Species diversity, change in forest cover and area of the Sundarbans, Bangladesh - Ahmed, Ashfaque; Ataullah, Md; Rashid, Parveen; Paul, Ashit Ranjan; Dutta, Sukumar; Ali, Md Shahjahan (Bangladesh Journal of Botany, 2018)
The phytosociological analysis, species diversity and types, fidelity, presence, constancy, Sørensen similarity index and changes in forest cover, land and water areas since 1972 were analyzed. Forty six species were recorded both in quadrats and growing outside which belong to 26 families and 41 genera, 19 were distinguished as true mangrove species and the rest were mangrove associates. Leguminosae and Rhizophoraceae were the dominant families represented by 5 spp. each. Three species were found to be invasive, namely Blumea lacera (Burm. F.) DC., Catharanthus roseus (L.) G. Don., Wedelia chinensis (Osbeck) Merr. The maximum importance value index was found in Heritiera fomes Buch.-Ham (48.08). The overall species diversity (H) of SMF was found 3.81, species richness (d) was 9.10 and evenness (e) was 0.47. The forest area was 385,237 ha in 2015. The satellite images showed that the forest and water area of SMF decreased gradually till 2015 in comparison to 1972. The bare land of Sundarbans showed a significantly increasing trend till 2015 since 1972.